Microvascular Free Flaps in Oral and Maxillofacial Reconstruction following Cancer Ablation - Yadav, Santosh Kumar; Shrestha, Suraksha (Journal of Nepal Health Research Council, 2017)
Microsurgical free flaps have become the first choice for reconstruction of oral and maxillofacial (OMF) defects after tumor resection. Till recently the pectoralis major myocutaneous flap (PMMC) was considered to be the benchmark for OMF reconstruction. This philosophy is changing fast with rapid advancement in reconstructive microsurgery. Years of innovation in reconstructive microsurgery has given us a reasonably good number of excellent flaps. Tremendous work has been put into producing some exceptionally brilliant research articles, sometimes contradicting each other. This has led to the need for clarity in some areas in this field. This article reviews the most common microvascular free flaps (MFF) namely, radial forearm free flap (RFFF), anterolateral thigh flap (ALT) and free fibula flap (FFF) that are commonly used in OMF reconstruction. Since they can cater to almost all sizeable defects we come across after ablative surgery in the OMF region, they can aptly be titled as the workhorses of OMF reconstruction with regard to free flaps.